Voice Changes After Thyroid Surgery: A Prospective Evaluation of Vocal Cord Function - Shah Roghani, Adil; Taj, Bakht; Arifullah, Arifullah; Jamil, Muhammad; Hafeez, Muhammad; Khan, Azam (Journal of Neonatal Surgery, 2025)
Background: Voice changes resulting from thyroid surgery complications due to recurrent laryngeal nerve injury or superior laryngeal nerve neuropraxia are common. These complications may hinder communication and significantly affect quality of life. Assessing the voice during the initial stages of postoperative rehabilitation assists in recognizing postoperative voice dysfunction so that rehabilitation potential may be optimized. Objectives: To evaluate incidence, patterns, and recovery of postoperative voice changes and vocal cord paralysis after thyroidectomy through voice analysis, laryngoscopy examination, and pre- and postoperative assessments. Methodology: this study conducted at Department Of ENT Kabir Medical College, Peshawar from july 2024 to dec 2024 a prospective study involving a cohort of 100 patients who underwent thyroid surgery. Preoperative and postoperative evaluations of vocal cord mobility, on the 7th day and 3 months, were conducted using fiber-optic laryngoscopy. The postoperative voice quality of the patients was assessed both perceptively and acoustically. The analyses were conducted using SPSS 24.0, and a significance level of p < 0.05 was applied. Results: Of the 100 studied patients, aged on average 42.6 years (SD 11.3), 22% had temporary changes in their voice, while 4% had voice dysfunction that was permanent. Laryngeal nerve paresis recurred within 6% of the cases (4 were unilateral, 2 were bilateral). On average Voice Handicap Index scores were significantly higher 7 days’ post op, then almost returning to baseline in 3 months’ post op (p=0.07). This score evaluated the handicap attributable to the voice. Injury to the superior laryngeal nerve impacted 8% of patients by removing the pitch of their voice, while the subjective increase in voice concern was perceived statistically significantly more in females (p=0.03). Conclusion: Thyroid surgeries are likely to induce temporary voice changes which resolve spontaneously. Routine preoperative and postoperative laryngoscopy are performed to mitigate the risk of permanent voice dysfunction, alongside meticulous surgical dissection and timely rehabilitation. Including voice evaluations as part of the thyroidectomy protocol has proven to enhance postoperative patient safety and satisfaction, particularly for patients whose occupation relies on voice use...